Respuesta europea al control judicial la discrecionalidad administrativa: Especial atención al test de racionalidad y al control de plena jurisdicción en el Derecho de la competencia - Soldevila Fragoso, Santiago (2022)
The jurisdictional control of Administration’s resolutions constitutes one of the central objects of Administrative Law. A modern State in which democratic principles must be reconciled with the efficiency of the Administration requires the adoption of clear and precise rules in order to delimit the extent of the jurisdictional control of the Administration. This need is more evident in the administrative-economic sphere, where the Administration enjoys a wide margin of discretionary action. In this context, the control of the rationality of administrative action is offered as an effective control technique, fully respectful for both Administration’s competences and fundamental rights of the administered.